Foundations of Bayesian theory - Edi Karni (The Johns Hopkins University, Department of Economics, 2005)
This paper states necessary and sufficient conditions for the existence, uniqueness, and updating according to Bayes rule, of subjective probabilities representing individuals beliefs. The approach is preference based, and the result is an axiomatic subjective expected utility model of Bayesian decision making under uncertainty with statedependent preferences. The theory provides foundations for the existence of prior probabilities representing decision makers beliefs about the likely realization of events and for the updating of these probabilities according to Bayes rule.
Keywords: D81; 330; Subjective expected utility; Bayesian theory; subjective probabilities.; Bayes-Statistik; Erwartungsnutzen; Theorie; Entscheidung bei Unsicherheit